2017
DOI: 10.1111/ans.14262
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative albumin ratio is associated with post‐operative pancreatic fistula

Abstract: Perioperative albumin ratio can predict POPF after PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
(77 reference statements)
2
12
1
Order By: Relevance
“…This relationship between DFA concentration and salivary fistula development was consistent with research by Larsen et al [6] which showed an upward trend in DFA concentration with early fistulisation. DFA concentration and perioperative albumin ratio has been reported to be an effective predictor of pancreatic fistula development after pancreatomy [7][8][9], also allowing an assessment for the earlier removal of the drain [10]. We speculate that the reason for the association between DFA concentration and salivary fistula development may be as follows.…”
Section: Discussionmentioning
confidence: 89%
“…This relationship between DFA concentration and salivary fistula development was consistent with research by Larsen et al [6] which showed an upward trend in DFA concentration with early fistulisation. DFA concentration and perioperative albumin ratio has been reported to be an effective predictor of pancreatic fistula development after pancreatomy [7][8][9], also allowing an assessment for the earlier removal of the drain [10]. We speculate that the reason for the association between DFA concentration and salivary fistula development may be as follows.…”
Section: Discussionmentioning
confidence: 89%
“…reviewed 225 PD cases including 40 patients with CR‐POPF and reported that the postoperative day 1 serum ALB level but not the preoperative ALB was significantly associated with the CR‐POPF 34 . The conclusion of Gruppo M's study 35 was similar to Xia W's. Thus, it remained more researches to solve the mystery.…”
Section: Discussionmentioning
confidence: 70%
“…Some authors reported that albuminemia reflects nutritional status and is independently associated with postoperative complications. In fact, hypoalbuminemia is related to postoperative morbidity and mortality as well as surgical site infection [ 35 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%